A holistic perspective on the theoretical foundations for ICT4D research. Issue 1 (2nd January 2019) - Sein, Maung K.; Thapa, Devinder; Hatakka, Mathias; Sæbø, Øystein
ABSTRACT: While many theories have guided research Information and Communication Technologies for Development (ICT4D), we are yet to construct a clear and coherent narrative that would help us answer the question of how ICT fosters development in underdeveloped communities. In this paper, we argue that one of the main reasons for this is that our holistic understanding of ICT4D is seldom grounded in theories to understand the core areas that define the field, namely, ICT, Development, and, '4' which are the transformative processes that link the two. Through a brief literature review, we list theories that have informed ICT4D research in each of these areas. We present examples of theories, namely, Capability Approach, Affordances, and Actor-Network Theory together with Social Capital and illustrate how we have used them in our research. Building on this holistic perspective on theoretical foundation, we propose five agendas for ICT4D research.